Improving continuity of care through the use of electronic records: A South African perspective - N. Mostert-Phipps; D. Pottas; M. Korpela (South African Family Practice)
The fragmented nature of modern healthcare provision makes it increasingly difficult to achieve continuity of care. As a result, strong emphasis is placed on the informational dimension of continuity of care. The importance of keeping medical records is noted. Paper-based methods of recordkeeping are inadequate with regard to supporting informational continuity of care. This has led to increased interest in electronic recordkeeping methods. This article describes the role that various electronic records, such as personal health records (PHRs), electronic medical records (EMRs) and electronic health records (EHRs), could play in improving informational continuity of care. A scalable approach, based on the adoption of standards-based PHRs and EMRs, with a standards-based health information exchange to enable the exchange of health information, is recommended for the South African healthcare sector. The possible impact of the envisaged National Health Insurance (NHI) on current, mostly paper-based recordkeeping systems, is also discussed. It is suggested that a start to the implementation of electronic records, is made at primary healthcare level. This is because the NHI will call on primary healthcare providers to act as gatekeepers to other levels of care. By ensuring that the bulk of patients’ health records are stored in electronic format, it would then be possible to exchange health information with other healthcare providers once they also adopted electronic records at a later stage.